De la nécessité d'une observation didactique pour accéder à l'épistémologie pratique des professeurs - Chantal Amade-Escot (Nantes Université, 2014)
This article is about the relevance of a didactical observation of ordinary teaching to account for "teachers' practical epistemology". Over the last years, teachers' knowledge, beliefs and know-how have been the focus of various research paradigms on teaching and became a substantial area of inquiry. In this paper, it is claimed that understanding teachers' practices needs to document in details how knowledge is enacted through didactical interactions within a pragmatic perspective of human activities. The paper gives an overview of the theoretical framework and the analytical tools used. The study of teacher and students didactical joint action allows depicting how knowledge is mobilized and the important role of teacher's practical epistemology in this process. Drawing on a body of works in physical education, three dimensions of the teacher's practical epistemology are then discussed through research excerpts.